Comparative effectiveness of anterior and posterior approaches for interscalene brachial plexus block: a systematic review and meta-analysis - Luis Eduardo Ciconini; Theodoro Beck; Catreen Abouelsaad; Karandip Bains; Mauren F. Carbonar (Brazilian Journal of Anesthesiology)
Introduction: Interscalene Brachial Plexus Blocks (ISBPB) are highly effective forms of anesthesia for surgeries involving the upper arm, shoulder, and neck. Recently, there has been a growing interest in comparing the advantages and limitations of the anterior and posterior approaches. Methods: This systematic review and meta-analysis aimed to determine whether the anterior or posterior approach to ISBPB offers a clinical advantage regarding complete block rates and time to block completion. We included randomized controlled trials comparing the anterior and posterior techniques for ISBPB while excluding studies with overlapping populations, comparisons of blocks other than interscalene, and articles written in a non-English language. Results: The search strategy identified 2229 articles, of which six Randomized Controlled Trials (RCTs) met the inclusion criteria for the meta-analysis. A total of 414 patients were included, with 210 patients in the anterior group and 204 in the posterior group. The Odds Ratio (OR) for a complete sensory block between the two techniques did not reach statistical significance (OR = 0.56 [0.20, 1.58], 95% CI, p = 0.27). Similarly, the Standardized Mean Difference (SMD) for the time to complete the block also did not reach statistical significance (SMD: -0.77 [-2.12, 0.59], 95% CI, p = 0.27). Heterogeneity for complete block was not significant (I2 = 0%), while procedure time showed high heterogeneity (I2 = 97%). Conclusion: Both techniques have shown effectiveness in providing surgical analgesia. The choice of technique should be determined by the provider's comfort and proficiency, as well as ensuring the highest level of safety for the patient.